EFL Teacher's Challenges and Strategies in Teaching Reading Comprehension Online - Novita Ika Prasetiya (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This research is carried out to investigate the challenges faced by EFL teachers in teaching reading comprehension online and to explore their strategies in teaching reading comprehension online. Three EFL teachers who teach reading comprehension online were the respondents. The data was collected by conducting an interview adopted from Utami (2020) and the researcher used semi-structured interviews.As results, there were some challenges faced by EFL teachers divided into three parts; in pre-reading, during-reading, and post-reading. The challenges in pre-reading are lack of student’s motivation, lazy to read long passage, reading is boring. Besides, the challenges in during-reading involve student’s insufficient vocabulary, students difficult to pronounce word well, poor reading ability. Not only that, the challenges in post-reading involve less of teacher’s preparation, low of student’s comprehension, teachers do not master the technology. On the other side, the teachers use some strategy at each stage. In pre-reading, the teachers use providing pictures or vocabulary and questions-answering strategy. In during-reading, the teachers use reading aloud, translation, quizzes strategy. In addition, in post-reading, the teachers use discussion also evaluation strategy.Furthermore, the result of the teacher’s interview showed that these strategies are effective to help students in the online learning process. For the teachers suggest to improve their quality in teaching in pre-, during-, and post-reading. Additionally, for future research suggests with more instruments and samples in data collection, such as questionnaire, observationKeywords: online reading class; teacher’s challenges; teacher’s strategies